Handgrip strength to screen early-onset sarcopenia in heart failure. (August 2022) - Blanquet, Marie; Massoulié, Grégoire; Boirie, Yves; Guiguet-Auclair, Candy; Mulliez, Aurélien; Anker, Stefan; Boiteux, Marie-Claire d'Agrosa; Jean, Frédéric; Combaret, Nicolas; Souteyrand, Géraud; Riocreux, Clément; Pereira, Bruno; et al.
Summary: Background & aims: Sarcopenia in heart failure (HF) is associated with severe outcomes, increased mortality, and high healthcare cost burden. Systematic muscle screening in patients with chronic HF would improve quality and appropriateness of care. Here we tested handgrip strength (HGS) as a screening tool for sarcopenia in patients with chronic HF, using the EWGSOP 2010 and 2019 reference-standard definitions of sarcopenia. Methods: HF inpatients, aged 65 years old or above, were prospectively included between November 2014 and September 2018, and relevant sociodemographic, anthropometric and HF characterization data was collected. The accuracy of HGS as a screening test for sarcopenia was assessed by gender using area under the receiver operating characteristic (ROC) curves (AUC). Results: The population consisted of 118 older patients (age: 78.9 yrs; BMI: 26.6 kg/m 2 ) with a mean HGS of 16.1 kg (SD 4.6) in women and 26.5 kg (SD 6.7) in men. Factors associated with HGS were age (p = 0.005), Instrumental Activity of Daily Living (p = 0.001), and heart rate (p = 0.034). Screening was positive (patients confirmed as sarcopenic by the HGS test) with cut-off values of 18 kg for women and 27 kg for men, with ROC analysis giving a sensitivity of 85.7% in women and 88.2% in men. Conclusions: HGS can be used as a valid tool to screen for sarcopenia in older (≥65 yrs) patients with chronic HF. Clinical trial registration: NCT03153774 . Highlights: Handgrip strength is a valid, valuable, and clinically practicable test for screening sarcopenia in chronic heart failure. Handgrip strength cut-off values of 18 kg in women and 27 kg in men gave 85.7% and 88.2% sensitivity, respectively. EWGSOP 2010 and 2019 definitions are congruent to diagnose severe sarcopenia.